Collaborative Evaluations: A Step-by-Step Model for the Evaluator - Wes Martz (The Evaluation Center at Western Michigan University, 2006)
A review of the book Collaborative Evaluations: A Step-by-Step Model for the Evaluator by Liliana Rodríguez-Campos published in 2005 by Llumina Press.